(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In this article, the content of amino acids in the fruit of Maclura pomifera growing in Uzbekistan and Turkey was determined and analyzed using the USSX method. 16 types of amino acids in the fruit of Maclura pomifera growing in Uzbekistan were studied by us. The content of amino acids in the fruit of Maclura pomifera growing in Turkey was determined by Rifat Battaloglu, a scientist at Nigde Omer Halisdemir University . In the fruit of Maclura pomifera growing in Uzbekistan, 1 gram of Maclura pomifera fruit extract contains 3.06 mg/g of proline, 2.39 mg/g of glycine , and 2.33 mg of histidine. In this, the effect of amino acids on human health was analyzed and studied based on scientific sources. The level of study of the obtained plant was calculated and it was concluded that the research is still insufficient.